2019
DOI: 10.17306/j.afs.2019.0642
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of pork loin marinated in kefir, yoghurt or buttermilk and cooked sous vide [pdf]

Abstract: Background. The most important qualities of meat and meat products include tenderness, juiciness and color. Sour meat marinating is a commonly used technique. In the available literature, there are no reports on the use of fermented dairy products (FDP) for meat marinating. The acids contained in FDP can improves the tenderness, taste, flavor, juiciness and color of meat products. The use of lower heat treatment temperature for a long time for cooking meat also positively affects its sensory properties and tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…[15] According to Mozuriene et al, [26] there is a positive effect of sour marinades on water capability, which can be correlated with swelling and/or increased extractiveness of myofibrillar proteins associated with an increase in ionic strength and a decrease in pH. [27][28][29][30] There was an increase in weight losses as temperature rose (P < .05) for beef cooked by sous vide technique. The obtained results agree with those found by authors who used sous vide technique to cook beef, [8,31,32] pork, [9] or lamb.…”
Section: Cooking Lossmentioning
confidence: 99%
See 3 more Smart Citations
“…[15] According to Mozuriene et al, [26] there is a positive effect of sour marinades on water capability, which can be correlated with swelling and/or increased extractiveness of myofibrillar proteins associated with an increase in ionic strength and a decrease in pH. [27][28][29][30] There was an increase in weight losses as temperature rose (P < .05) for beef cooked by sous vide technique. The obtained results agree with those found by authors who used sous vide technique to cook beef, [8,31,32] pork, [9] or lamb.…”
Section: Cooking Lossmentioning
confidence: 99%
“…[8] Likewise, it should be noted that, in addition to water, other water-soluble components are lost during cooking. The losses of these components are limited with the sous vide technique, [29] and if collagen solubilization temperature is achieved during cooking, after cooling, the soluble protein with the water and together with sarcoplasmic proteins form gelatin. [9] The obtained results for meat analog showed that only the cooking temperature significantly affected cooking losses (P < .05).…”
Section: Cooking Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of scientific studies [9][10][11][12] show that the presence of live lactic acid bacteria (LAB) cultures in buttermilk and acid whey is widely used in the meat industry, it can extend the shelf life of marinated pork and beef, inhibit oxidative processes and improve the sensory properties and tenderness of meat products. Lactic acid, its salts and lactic acid bacteria cultures are used to preserve food [13], and the addition of LAB is justified in the production of raw cold meat, especially fast-ripening and fermented [14][15]. The use of LAB with antimicrobial properties helps to limit the addition of chemical preservatives to food [1,[16][17].…”
Section: A C C E P T E Dmentioning
confidence: 99%